Impairment of dynamic pressure autoregulation precedes clinical deterioration after aneurysmal subarachnoid hemorrhage - Fontana, Johann; Wenz, Holger (Journal of neuroimaging, 2016)
Background: This study was designed to evaluate the potential of the dynamic autoregulation index (ARI) to serve as an early warning system for an imminent clinical deterioration after subarachnoid hemorrhage (SAH). Methods: All patients received a baseline digital subtraction angiography and a computed tomography (CT) prior to treatment. The clinical status, the ARI, and the transcranial Doppler (TCD) values were evaluated daily until discharge from the intensive care unit (ICU). A CT scan at least 10 days after the postictal event was used to determine the occurrence of delayed infarcts. Results: 20 patients were prospectively included in the study. 3 refused further participation between days 2 and 3. Patients with no significant deteriorations of the clinical status and no proximal vasospasm (VS) in the middle cerebral artery (MCA)/delayed infarcts showed a significant positive linear regression of the ARI values in both hemispheres from day 1 till 11 (ARI right: 2.7 + .31/day, ARI left: 2.8 + .27/day; P < .01). All patients with angiographic VS of more than one-third in the MCA showed a corresponding drop of the ARI to values ≤1.7. The ARI drop occurred 2.5 (±1.3) days prior to significant deteriorations of the clinical status, increase of TCD values or the detection of angiographic cerebral VS/delayed infarcts in the corresponding hemispheres. Conclusion: The results demonstrate the capability of the ARI to serve as a reliable early warning system after SAH. Further trials with larger study populations are needed to validate these promising preliminary data.
Gesehen am 21.05.2019
First published: 21 September 2015